Identification of Factors in Selection of Islamic Education Management Postgraduate Programs - Suratin, Sonia Isna; Mutniati, Vebri Putri; Gazali, Ahmad; Latif, Abdul; Latif, Muhammad Sabri; Rosyida, Fatia Ainur (Yayasan Indonesia Emerging Literacy Education, 2024)
In facing global challenges, there needs to be a major contribution to Islamic Education Management to optimize the career orientation of postgraduate students. This research provides insight into the factors that influence students in choosing a study program. The objectives of this research: 1) Provide insight into the decision-making process of postgraduate students at UIN Maulana Malik Ibrahim Malang in choosing the Islamic Education Management study program, 2) Identify the most relevant factors that influence the choice of study program. The approach used in this research is a qualitative approach with a case study at the Postgraduate Program at UIN Maulana Malik Ibrahim Malang. The data collection techniques are through semi-structured interview techniques and documentation. Meanwhile, the data analysis techniques in this research include 3 methods, namely: Data reduction, data presentation, and drawing conclusions from the data. The findings of this research include: 1) Students chose to continue their studies at the UIN Maulana Malik Ibrahim Malang Postgraduate Program for self-development and career advancement in the future, 2) The UIN Maulana Malik Ibrahim Malang Campus was chosen because of its good reputation, superior study program accreditation, and a positive brand image, 3) A diverse undergraduate educational background is not an obstacle in choosing an MPI study program, 4) Factors such as job prospects, advice from lecturers, and family influence play an important role in choosing an MPI study program. The conclusion of this research provides an in-depth understanding of the factors that influence students' decisions in choosing the Islamic Education Management study program at UIN Maulana Malik Ibrahim Malang in the 2022/2023 academic year.